The Influence of Extracurricular Sports Activities on the Psychological Resilience of Middle School Students - Chen, Nuo (Transactions on Social Science, Education and Humanities Research, 2024)
The level of psychological resilience is an important aspect of measuring mental health. In recent years, many middle school students in China have psychological problems due to excessive learning pressure and weak anti-pressure ability. Extracurricular sports activities in physical exercise are an effective way to improve the level of psychological resilience of middle school students. Based on this, China continues to attach importance to extracurricular physical exercise, so as to alleviate students ’ psychological pressure and promote students ’ mental health. Based on the adolescent psychological resilience scale, this paper analyzes the influence of different types of extracurricular sports activities on the psychological resilience of middle school students in China. This study found that in the school extracurricular sports activities, sports associations, sports students, school sports teams mainly in interpersonal assistance, emotional control, goal focus on three aspects to improve the level of psychological resilience of middle school students. In off-campus sports activities, extracurricular sports training and spontaneous extracurricular sports activities mainly have a positive impact on students ’ psychological resilience level in family support and positive cognition. Secondly, this study puts forward three suggestions for the development of extracurricular sports activities in modern China : schools organize diversified extracurricular sports activities ; parents improve the awareness of cultivating children ’s interest in physical exercise ; the society provides public fitness and sports facilities for middle school students. The significance of this study is to improve the attention of the state, schools and parents to extracurricular sports activities, promote the further development of extracurricular sports activities, and improve the physical quality and psychological resilience of middle school students.